Bridging Data Pasien Rawat Inap Dengan INA-CBG’s (Indonesian Case Base Groups’s) - Ahmad Kurniawan; Krisna Widatama; Ike Yunia Pasa (Jurnal Sistem Cerdas, 2022)
Abstract— Integration and acceleration of data transactions is a very important issue to be discussed in the era of integrated information technology development. This problem is the reason for making the system interact with each other quickly. Indonesian Case Base Groups (INA-CBG's) is an application used to process claims for National Health Insurance (JKN) participants from the Hospital. Every hospital is required to send patient data through INACBG's. However, current data claims for inpatients are still done manually. This manual process will make officers enter patient data into the main system and INACBG's. This results in the efficiency of work performed by hospital staff. In addition, the data entered is not automatic because there is a delay when entering data into the main system and INACBG's. Development of an Inpatient Information System that is integrated with INA-CBG's using JavaScript Object Notation (JSON). This format can send inpatient claim data to the INACBG's application in the form of an array. The JSON format does not have a standard format for writing, so it can be faster and more flexible in sending data. With an integrated system between the main system and INACBG's, it can increase the efficiency of processing data claims to INACBG's.